2004
DOI: 10.1001/archsurg.139.6.614
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Subareolar and Periareolar Injection Techniques for Breast Sentinel Lymph Node Biopsy

Abstract: Subareolar or periareolar injection of radioactive technetium sulfur colloid is equivalent to other injection techniques for breast cancer sentinel lymph node (SLN) biopsy.Design and Setting: Prospective, multicenter clinical trial.Patients: A total of 3961 individuals with clinical stage I and II breast cancer.Interventions: All patients underwent attempted SLN biopsy followed by completion axillary dissection. Injection technique was determined by the preference of each participating surgeon. Most surgeons h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 31 publications
(66 reference statements)
3
47
2
7
Order By: Relevance
“…The NEW START programme recommends the combined technique of radiocolloid and blue dye injection injected in a superficial plane for SLN localisation. This has been well validated, is easy to teach and use, is predictable, has rapid migration, high radiocolloid nodal uptake resulting in improved image quality and high SLN identification rates with comparable false negative rates to other techniques (8).…”
Section: Introductionmentioning
confidence: 99%
“…The NEW START programme recommends the combined technique of radiocolloid and blue dye injection injected in a superficial plane for SLN localisation. This has been well validated, is easy to teach and use, is predictable, has rapid migration, high radiocolloid nodal uptake resulting in improved image quality and high SLN identification rates with comparable false negative rates to other techniques (8).…”
Section: Introductionmentioning
confidence: 99%
“…A large multi-centre clinical trial published by Chagpar et al [42] reported an identification rate of 91.1% for peritumoral injections, that contrasts with the 99.3% rate achieved when the patients in the same study underwent sub-areolar injections. Gross tumor involvement of the nodes may also impair the uptake of both the radiopharmaceutical (detected by imaging and/or the gamma probe) and by the blue dye resulting in failure in isolating the true SN [19].…”
Section: Discussionmentioning
confidence: 87%
“…Despite refinements in injection techniques that have led to near 100% SLN identification in some studies, 1,4,5 variable FN rates have raised concern about the staging accuracy of this procedure. As with most diagnostic tests, SLN biopsy is not 100% sensitive: it does not infallibly detect nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%